FGF-2 disrupts mitotic stability in prostate cancer through the intracellular trafficking protein CEP57 - Cuevas, Rolando; Korzeniewski, Nina; Tolstov, Yanis; Hohenfellner, Markus; Duensing, Stefan (Cancer research, 2013)
Malignant tumors with deregulated FGF-2 expression such as prostate cancer are also frequently aneuploid. Aneuploidy can be caused by cell division errors due to extra centrosomes and mitotic spindle poles. However, a link between FGF-2 overexpression and chromosome missegregation has so far been elusive. Here, we show that FGF-2 rapidly uncouples centrosome duplication from the cell division cycle in prostate cancer cells through CEP57, an intracellular FGF-2-binding and trafﬁcking factor. CEP57 was initially identiﬁed as a regulator of centriole overduplication in an RNA interference screen. We subsequently found that CEP57 rapidly stimulates centriole overduplication and mitotic defects when overexpressed and is required not only for FGF-2-induced centriole overduplication but also for normal centriole duplication. We provide evidence that CEP57 functions by modulating tubulin acetylation, thereby promoting daughter centriole stability. CEP57 was found to be overexpressed on the mRNA and protein level in a subset of prostate cancers, of which the vast majority also showed FGF-2 upregulation. Taken together, our results show an unexpected link between altered microenvironmental signaling cues such as FGF-2 overexpression and mitotic instability and provide a rationale for the therapeutic targeting of the FGF-2/FGFR1/CEP57 axis in prostate cancer. Cancer Res; 73(4); 1400-10. Ó2012 AACR.
Published online first December 12, 2012
Gesehen am 17.04.2018